The literary manager's toolkit : a practical guide for the theatre - Healy, Sue (Susan Ann) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Literary Manager's Toolkit is a clear and comprehensive guide to the role of the literary manager in theatre and beyond, focusing on the key skills, networks and processes that underpin a successful career in this and associated roles. This book outlines the tasks and responsibilities of a literary manager in the selection, development, and production of new plays. In the first part, it outlines the how, when and why of the literary manager's main activities equipping the reader with everything that they will need when approaching this role's central challenges. The second part provides a selection of practical, accessible and easy-to-follow materials and workshop suggestions for literary managers who will work with playwrights as they develop their creative writing and dramaturgy skills. This is the go-to resource for the working professional literary manger or dramaturg, and for students on dramaturgy courses in theatre degree programmes"--
An evolving and elusive job description -- Attracting unsolicited scripts -- Systems, structures and approaches -- Dramaturgy -- Supporting and nurturing new writers -- Diversity and inclusion -- To pay or not to pay -- Life after literary management -- The literary manager as teacher.
Keywords: Theater -- Production and direction -- Great Britain; Dramaturges -- Vocational guidance -- Great Britain; Theater -- Vocational guidance -- Great Britain; PERFORMING ARTS / Theater / Direction & Production; PERFORMING ARTS / Theater / Playwriting; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing